Dietary protein energy supplementation of pregnant Asian mothers at Sorrento, Birmingham. II: Selective during third trimester only. Issue 6342 (28th August 1982) - Viegas, O A; Scott, P H; Cole, T J; Eaton, P; Needham, P G; Wharton, B A
Abstract : Unselective dietary protein energy supplementation of Asian mothers at Sorrento Maternity Hospital did not enhance intrauterine growth. The effect of selective supplementation was therefore studied. Forty-five mothers who at 28 weeks were known to be nutritionally at risk (triceps increment less than or equal to 20 microns/week between 18 and 28 weeks) received one of three supplements during the third trimester: (a) vitamins only--a multivitamin sachet daily containing vitamins A, B, C, and D; (b) energy--42-125 MJ (10 000-30 000 kcal), all from carbohydrate, plus vitamins; (c) protein energy--energy and vitamins as before, but with 5-10% of energy from milk protein. Eighty-three mothers regarded as adequately nourished at 28 weeks also received one of the three supplements. In the nutritionally at-risk mothers the protein energy supplement was associated with a heavier crude birth weight and heavier weight for gestational age. Supplementation did not lead to improved intrauterine growth in those mothers who were adequately nourished. The differential effect of supplementation depending on the mothers' nutritional state during the second trimester may explain apparently conflicting results of other studies where some have shown a substantial effect of supplementation and others only a small effect. This effect of intervention is further evidence that "poor nutrition" contributes to poor intrauterine growth in selected mothers, even in developed countries.